Hadith #4012 - Sunan Abi Dawud - Abdul Malik bin Aby عبد الملك بن أبي سليمان; Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; Ata' bin Abi Rabah عطاء بن أبي رباح; Muhammad bin Ahmed bin Abi Khalaf محمد بن أحمد بن أبي خلف; Safwan bin Y'ala bin Umayya صفوان بن يعلى بن أمية; Ya'la bin Umayya (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) saw a man washing in a public place without a lower garment. So he mounted the pulpit, praised and extolled Allah and said: Allah is characterised by modesty and concealment. So when any of you washes, he should conceal himself.
Grade: Sahih

Hadith #4625 - Sunan Abi Dawud - Abdul 'Aziz bin Abi Salma b. 'Ubaidulla عبد العزيز بن أبي سلمة بن عبيد الله; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Uthman bin Muhammad (Sunan Abi Dawud)
Al-Hasan said: I will never return to it.
Grade: Sahih

Hadith #4791 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; Mujahid bin Jabir مجاهد بن جبر; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
A man asked permission to see the Prophet (ﷺ), and he said: He is a bad son of the tribe, or: He is a bad member of the tribe. He then said : Give him permission. Then when he entered, he spoke to him leniently. `A’isha asked : Apostle of Allah! You spoke to him leniently while you said about him what you said! He replied: The one who will have the worst position in Allah’s estimation on the Day of Resurrection will be the one whom people left alone for fear of his ribaldry.
Grade: Sahih

Hadith #4878 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; Abu Burzah al-Aslami; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) said: When I was taken up to heaven I passed by people who had nails of copper and were scratching their faces and their breasts. I said: Who are these people, Gabriel? He replied: They are those who were given to back biting and who aspersed people’s honour. Abu Dawud said: Yahya b. ‘Uthman has also transmitted it from Baqiyyah, there is no mention of Anas in it.
Grade: Sahih

Hadith #5199 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Umar ibn al-Khattab (Sunan Abi Dawud)
one who is riding should salute one who is walking. He then mentioned the rest of the tradition.
Grade: Sahih